2009
DOI: 10.1093/pasj/61.6.1375
|View full text |Cite
|
Sign up to set email alerts
|

Solar-Radiation Heating Effects on 3200 Phaethon

Abstract: Apollo-type near-Earth asteroid 3200 Phaethon, having a small perihelion distance of $q$$\sim$ 0.14 AU, is classified as F- or B-type, one of subclasses among the C-complex (C-, G-, B-, and F-types) asteroids. The F/B-type asteroids and dehydrated CI and CM carbonaceous chondrites, which are regarded as being linked to each other, underwent a thermal history of high-temperature heatings at more than hundreds of degrees and dehydration for a certain period of time after aqueous alteration in their parent bodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 51 publications
6
71
2
Order By: Relevance
“…An effective upper limit is given by the subsolar temperature on a non-rotating body (or on one having a spin vector aligned with the Sun), which could reach T = 1050 K at q = 0.14 AU. The peak dayside temperatures are thus contained in the range 746 < T < 1050 K, in agreement with more complicated thermal models (Ohtsuka et al 2009). For comparison, dayside aphelion temperatures will be smaller by the factor ((1+e)/(1−e)) 1/2 ∼ 4, corresponding to 180 K and 256 K for the low and high temperature limits, respectively.…”
Section: Dustsupporting
confidence: 81%
“…An effective upper limit is given by the subsolar temperature on a non-rotating body (or on one having a spin vector aligned with the Sun), which could reach T = 1050 K at q = 0.14 AU. The peak dayside temperatures are thus contained in the range 746 < T < 1050 K, in agreement with more complicated thermal models (Ohtsuka et al 2009). For comparison, dayside aphelion temperatures will be smaller by the factor ((1+e)/(1−e)) 1/2 ∼ 4, corresponding to 180 K and 256 K for the low and high temperature limits, respectively.…”
Section: Dustsupporting
confidence: 81%
“…If the spin state had an obliquity of ∼90 • (Krugly et al 2002;Ansdell et al 2014), one of the hemispheres of Phaethon would receive substantially more solar heating during the perihelion passage because it is always facing the Sun. But Ohtsuka et al (2009) reported no significant spectral variability across the body, which might indicate that, contrary to expectations (Hiroi et al 1996), the sun-driven heating does not affect the spectral properties. Alternatively, Phaethon may not always be exposing the same hemisphere at perihelion, or the reason for the obliquity might be a combination of both explanations.…”
Section: Introductioncontrasting
confidence: 65%
“…This means that 500 yr ago, and again 4 kyr ago, it was the southern hemisphere's turn to be irradiated at perihelion. This probably is the reason why Phaethon's surface does not show any convincing hemispheric spectral or color asymmetry (Ohtsuka et al 2009). Additionally, we wonder whether these polar-irradiation cycles, together with variations in perihelion distance, play a role in the strength of Phaethon's activity and thus possibly in the origin of different components of the Geminids stream.…”
Section: Spin Evolutionmentioning
confidence: 99%
“…For example, asteroid (3200) Phaethon, the parent body of the Geminid meteoroid stream, has shown recurrent activity around its perihelion q ∼ 0.14 AU (Jewitt & Li 2010;Jewitt et al 2013; where the surface temperature reaches 750 K T 1100 K (Ohtsuka et al 2009). Phaethon is essentially a "rock comet" and the activity is caused by the production of small dust particles with radii ∼1 μm due to thermal fracture and decomposition cracking of hydrated minerals (not sublimation of ice).…”
Section: Discussionmentioning
confidence: 99%
“…The Geminid meteoroids show extreme diversity in their Na abundance, from strong depletion to near Sun-like Na content (Harvey 1973;Borovička et al 2005;Kasuga et al 2005). Presumably, this compositional diversity reflects different thermal modification on Phaethon (or perhaps the larger sized precursor body) itself Kasuga et al 2006;Ohtsuka et al 2006;Kasuga & Jewitt 2008;Capek & Borovička 2009;Kasuga 2009;Ohtsuka et al 2009). For the Quadrantid meteoroids, the measured line intensity ratios show that Na is less depleted than in the majority of Geminid meteoroids (Koten et al 2006;Borovička et al 2010).…”
Section: Discussionmentioning
confidence: 99%